Cohort profile: maternal and child health and parenting practices during the COVID-19 pandemic in Ceará, Brazil: birth cohort study (Iracema-COVID). Issue 6 (1st June 2022) - Castro, Marcia C; Farías-Antúnez, Simone; Araújo, David Augusto Batista Sá; Penna, Ana Luiza; Oliveira, Francisco Ariclene; de Aquino, Camila Machado; Lima Neto, Antônio Silva; de Sousa, Geziel dos Santos; Tavares Machado, Marcia Maria
Abstract : Purpose: Maternal and child health and parenting practices during the COVID-19 pandemic in Ceará (Iracema-COVID) is a longitudinal, prospective population-based birth cohort designed to understand the effects of the pandemic and social withdrawal in maternal mental health, child development and parenting practices of mothers and families. Participants: A sample of mothers who gave birth in July and August 2020 (n=351) was enrolled in the study in January 2021. Interviews were conducted by telephone. Data were collected through standardised questionnaires that, in addition to sociodemographic and economic data, collected information on breast feeding, mental health status and COVID-19. Findings to date: Results from the first wave show that the majority of participants have 9–11 years of schooling (54.4%; 95% CI 61.0 to 70.9) and are of mixed race (71.5%; 95% CI 66.5 to 76.0). At the time of the survey, 27.9% of the participants were out of the labor force (95% CI 23.5 to 32.9) and 78.6% reported a decrease in family income after restrictions imposed due to the pandemic (95% CI 74.0 to 82.6). The prevalence of maternal common mental disorder symptoms was 32.5% (95% CI 27.8 to 37.6). Future plans: Follow-up visits are planned to occur every 6 months for the next five years (2021–2025). Additional topics will be included in future waves (eg, food insecurity and parenting practices). Communication strategies for bonding, such as picture cards, pictures of mothers with their children and phone calls to the participants, will be used to minimise attrition. Results of this prospective cohort will generate novel knowledge on the impact of the COVID-19 pandemic on maternal and child health and parenting practices in a population of women and children living in fifth largest city of Brazil.